(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The purpose of this study is to look at how to incorporate creative thinking and writing strategies in English language schools. Written discourse has been shown to be a difficult part for foreign language learners to master, and educators should look for new ways to teach it. Student-centered and self-initiated approaches for increasing writing skills are largely studentcentered and self-initiated as they get more autonomy to improvise and express their ideas and perceptions freely by examining new vocabulary, grammar patterns, and linguistic strategies. In this article discusses about fact, information and some useful methods the developing thinking skills through creative writing.